Quiz Book for clever kids (London Buster Books, 2015)
From the author of the bestselling Brain Games for Clever Kids, this quiz book will keep clever kids entertained for hours. It's jam packed full of quizzes to complete! Conveniently compact for travelling, this book is perfect for clever kids who love to truly test their brain power. The book has over 600 questions to keep even the cleverest of kids entertained, from science and nature to history and geography. Jam-packed with 10 different kinds of quiz such as 'true or false' and multiple choice to keep kids on their toes, it's impossible to get bored of these brain busters. There are three difficulty levels so kids can either work their way to the top or give themselves the ultimate challenge! Other books in the series include: 9781780552491 Brain Games For Clever Kids 9781780553078 Wordsearches for Clever Kids 9781780553085 Crosswords for Clever Kids 9781780555409 Maths Games for Clever Kids 9781780554723 Brain Gaming for Clever Kids Coming soon: 9781780555621 Times Tables Games for Clever Kids 9781780554730 Word Games for Clever Kids
Keywords: Kids Book- Quiz Books